Bahasa dan Budaya Sebagai Cerminan Kepribadian Seseorang Perspektif Kasus Budaya Jawa - Anisa Niwanda; Muhammad Alfi Harahap; Putri Rahmadani (PUSTAKA: Jurnal Bahasa dan Pendidikan, 2024)
Language is one of the main reflections of a person's personality. Through language, abstract thoughts that occur in the human brain can be expressed and understood by other people. The thought process embodied in words and language can influence actions, behavior, habits, and ultimately shape a person's character. The method for writing this article is qualitative with a literature study approach. Character formed from good habits will bring success and prosperity, while bad character will lead to failure. Language and culture have a close relationship and influence each other. Language is a part of culture that functions as a means of communication and a means of cultural development. Language speakers develop vocabulary and ways of speaking according to their experiences and cultural values. Therefore, language reflects not only individual personality, but also the cultural identity of society. The relationship between language, behavior and culture attracts the attention of many experts from various scientific disciplines. Some views view language as a subordinate part of culture, while others consider language and culture to have an equal coordinative relationship. In this context, language not only influences the way of thinking and acting, but also reflects the values ​​and norms that apply in society. The influence of globalization on local languages ​​and culture is also a concern. Even though there are concerns about the extinction of regional languages, such as Javanese, the enthusiasm to preserve and develop local languages ​​and culture remains strong. Awareness of the importance of language as a means of communication and cultural identity must be increased to face the challenges of globalization. In conclusion, language structure can influence the structure of perception and behavior, and vice versa. Therefore, an in-depth study of the relationship between language, behavior and culture is needed to ensure the continuity and development of local culture amidst global cultural influences.